2020
DOI: 10.1007/s00256-020-03579-6
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant calciphylaxis and COVID-19 associated thrombotic retiform purpura

Abstract: While initial reports regarding coronavirus disease 2019 (COVID-19) focused on its pulmonary manifestations, more recent literature describes multisystem abnormalities related to its associated microvascular angiopathy. Calciphylaxis is a rare systemic condition characterized by tissue necrosis in the setting of systemic microvascular calcifications. Both COVID-19 and calciphylaxis are procoagulant diagnoses associated with vascular-mediated cutaneous findings. To our knowledge, this is the first report to doc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 31 publications
0
20
0
2
Order By: Relevance
“…There is an increased risk of venous and arterial complications related to COVID‐19, including deep vein thrombosis, pulmonary embolism, ischemic stroke, myocardial infarction, and acute kidney injury. To date, calciphylaxis has been observed in two COVID‐19 patients, one with end‐stage renal disease and the other being treated with warfarin 4,5 . Our patient was nonuremic and did not receive warfarin.…”
Section: Figurementioning
confidence: 77%
See 1 more Smart Citation
“…There is an increased risk of venous and arterial complications related to COVID‐19, including deep vein thrombosis, pulmonary embolism, ischemic stroke, myocardial infarction, and acute kidney injury. To date, calciphylaxis has been observed in two COVID‐19 patients, one with end‐stage renal disease and the other being treated with warfarin 4,5 . Our patient was nonuremic and did not receive warfarin.…”
Section: Figurementioning
confidence: 77%
“…To date, calciphylaxis has been observed in two COVID-19 patients, one with end-stage renal disease and the other being treated with warfarin. 4,5 Our patient was nonuremic and did not receive warfarin.…”
mentioning
confidence: 86%
“…(Rotman et al, 2020) report a case of a rare syndrome of calciphylaxis and COVID-19 in which calcium was deposited in the vasculature and associated in this case with ischaemic dermopathy. In retrospective cohort study in a tertiary-care hospital (Di Filippo et al, 2020) found hypocalcaemia in 82% of 531 patients with COVID-19.…”
Section: Resultsmentioning
confidence: 99%
“…30 The more recent reports documenting laboratory-confirmed SARS-CoV-2 infection can be seen in Table 5. [30][31][32][33][34][35][36][37][38][39][40][41][42] Although more reports have emerged, there is still limited evidence-based reports regarding the predictive prognosis and significance of timeline of these dermatologic signs.…”
Section: Discussionmentioning
confidence: 99%